Market Reforms and Commercial Agreements in Latin America (1970-2015) [Reformas de Mercado y Acuerdos Comerciales en América Latina (1970-2015)] - Cuevas-Ossandon, R (Universidad Nacional Autonoma de Mexico, 2019)
Between 1970 and 2015, Latin America experienced a steady increase in their Free Trade Agreements put in force. Also, in this period important changes were introduced in them economic systems, through the introduction of market reforms. In the paper, it was argued that the implementation of this type of instruments is explained to a greater extent by the implementation of market reforms over other variables indicated in the specialized literature, such as higher levels of democratization. © 2019 Universidad Nacional Autonoma de Mexico. All rights reserved.